A promising marker in patients with coronary artery ectasia: Uric acid / HDL ratio - Kurtar Mansiroglu, Asli; Cosgun, Mehmet; Sincer, Isa; Gunes, Yilmaz (Annals of Medical Research, 2021)
Aim: Elevated levels of uric acid and low levels of high-density lipoprotein (HDL) cholesterol are associated with cardiovascular events and mortality. We investigated a novel marker, uric acid/HDLratio (UHR), in coronary artery ectasia patients (CAE). Materials and Methods: The present study included 104 patients (58 male, 46 female; mean age, 61±12 years) diagnosed as having isolated CAE and 110 controls (44 male, 66 female; mean age, 60±12 years) whose coronary artery findings were normal as revealed by coronary angiography. Medical records of all the patients were reviewed and the data were collected retrospectively. Baseline characteristics, hematologic and biochemistry parameters were recorded, and we calculated the value of UHRResults: The CAE group had significantly higher values of uric acid (6.48±1.62 vs. 5.37±1.12; p0.001) and UHR (0.15±0.05 vs. 0.11±0.05; p0.001). Spearman’s correlation test showed a significant association of uric acid and UHR with CAE (r=0.40, p0.001 and r=0.51, p0.001, respectively). On the other hand, HDL had a negative correlation with the presence of CAE (r=0.44, p0.120 UHR (%) values had a sensitivity of 72% and specificity of 68% for the determination of CEA.Conclusion: We observed in our study the finding in which the uric acid and UHR values were higher in individuals with CAE compared to non-CAE subjects. There was an association between UHR and CAE.
Keywords: Coronary artery ectasia; uric acid; uric acid/ HDL ratio